A Graph Theoretical Analysis of the Web Using DNS Traffic Traces - Sanders, Sean; Kaur, Jasleen (Proceedings - International Symposium on Modeling, Analysis, and Simulation of Computer and Telecommunication Systems, 2015)
The structure of the web has been extensively studied using HTML-based data. However, the increase in dynamic and personalized content has made the analysis of HTML-based data more difficult. A viable alternative to studying the web using HTML data is to study the web using DNS traffic traces. In this paper, we conduct a preliminary study to investigate the question - What can DNS traffic traces tell us about the structure of the web? In particular, we analyze the connectivity properties of this web graph by using eigenvalue analysis and spectral clustering. We also discuss the implications of this analysis with respect to web development and user privacy.